English Language Teacher Agency in Response to Curriculum Reform in China: An Ecological Approach - Wang, Lian (Frontiers in Psychology, 2022)
This paper draws on the ecological perspective of teacher agency to examine the manifestation of English teachers’ agency toward the ongoing curriculum reform in China and the factors that impact it. This study surveyed 353 high school English teachers and then collected data from three case study participants through in-depth interviews. The findings showed that the majority of teachers surveyed exhibited positive attitudes and beliefs about implementing the reform and inclinations to change, but the teachers also showed a constrained state of agency in practice. Teacher agency developed as the teachers exerted sustained pedagogical change and reflection on reform-based practices. Through the findings, prior experiences and reform-oriented beliefs were found to mediate teachers’ agency, and reform-related experiences were more influential than future goals in shaping agency. The factors of perceived school culture that involved teachers’ interaction with students, colleague cooperation and administrative support also medicated teachers’ agency in practice. Implications are proposed for policy-makers and school leaders to help teachers coordinate inconsistencies between high-stakes examination preparation and holistic education and make positive sense of professional development in the context of educational changes.